The Ballad of Sexual Dependency (1996) di Nan Goldin e la teoria della rappresentazione di Louis Marin - Coco, Lucia (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
The essay focuses on Louis Marin’s theory of representation and, in particular, on its duplex nature: transparency and opacity. Some images from The Ballad of Sexual Dependency by Nan Goldin will be analyzed, stressing all those aspects and mechanisms that Marin classifies under the concept of opacity. Showing its own tools, The Ballad becomes a way of representing a world that comes with a fundamental asymmetry in respect to the viewer.